Answer:
Step-by-step explanation:
x + 4 = 2x + 1
-x -x
4 = 1x + 1
-1 -1
3 = 1x
-- --
1 1
3 = x
Check:
3 + 4 = 2(3) + 1
7 = 6 + 1
7 = 7
Answer:
6 seconds after it is launched
Step-by-step explanation:
h(t) = -4t² + 16t + 48
The balloon is at ground level when it lands.
When it is launched, t = 0, and h(0) = 48
When it lands, at time t, h(t) = 0.
-4t² + 16t + 48 = 0
t² - 4t - 12 = 0
(t - 6)(t + 2) = 0
t = 6 or t = -2
The balloon will hit the ground 6 seconds after it is launched.
Answer:
b
Step-by-step explanation:
the answer is b if values are plugged in to function
Answer:complete questions
Step-by-step explanation:
Answer:
- 8x > 24
Step-by-step explanation:
Given
- 6x - 10 > 14 + 2x ( subtract 2x from both sides )
- 8x - 10 > 14 ( add 14 to both sides )
- 8x > 24 ← required missing step
Divide both sides by - 8, reversing the symbol as a result of dividing by a negative quantity.
x < - 3 ← is the solution